Isolation, Identification and Antibiogram of Cloacal Flora from Apparently Healthy Caged Zoo Birds - Golaviya, Akash V.; Pandya, Suchit S.; Patankar, Pratyush G.; Joddha, Harshrajsinh B.; Chavda, Chirag M.; Bhanderi, Bharat B.; Jhala, Mayurdhvaj K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Antibiotics are routinely used in animals and birds to prevent and cure bacterial infections. Various multidrug resistance bacteria have been detected in caged zoo birds, however there is a little known about their resistance pattern. In current study we isolated and identified cloacal bacteria from 50 zoo birds and compared their antimicrobial susceptibility. A total of 28 cloacal samples (56%) were found positive for different bacteria by selective culture. The bacteria isolated from different types of caged birds were Escherichia coli (26%), Staphylococcus spp. (8%), Streptococcus spp. (4%) and some unidentified Gram-positive and Gram-negative bacteria (14%). Of these isolates, E. coli was the most frequent isolate. The results of antibiotic sensitivity tests revealed that cefotaxime and sulphadiazine were highly (>60%) resistant to isolated cloacal microflora of zoo birds. However, the antibiotics such as ceftriaxone and amikacin showed moderate to high sensitivity against almost all the bacterial isolates. Of these, co-trimoxazole was found to be consistently highly effective (100%) on all the E. coli isolates. Overall, the results showed that zoo birds can be carrier of multidrug resistant organisms including Escherichia coli.
Keywords: Antibiotic sensitivity; Cloacal flora; Escherichia coli; Zoo birds